Adolescent Focused Intervention Bundle for Institutionalized Adolescents\' Health Promotion: A Study Protocol - Joy Sandhya Joseph; Kanniammal Chinnathambi (Iran University of Medical Sciences, 2024)
Background: A relatively large part of the global burden of diseases has roots in adolescence, caused by social, environmental, and behavioral characteristics rather than genetic, congenital, or biological origins. Adolescents with unhealthy behaviors are more likely to suffer from emotional and behavioral problems (EBPs) and nutritional issues such as iron deficiency anemia (IDA), leading to poor physical and social status and behavioral health insufficiencies. The sustainable development goals place a strong emphasis on adolescent health promotion, and UNESCO urges this noble aim to use an integrated approach to interventions. Moringa-incorporated snacks reduce iron deficiency and reduce the incidence of anemia. Comparably, mindful mandala art therapy fosters resilience and, when paired with life skill training, can lessen EBPs, supporting mental health. When combined, these evidence-based treatments may promote adolescent health. This paper aims to introduce the protocol related to investigating the effect of an adolescent-focused intervention bundle (AFIB) on adolescent health promotion by evaluating changes in hematological parameters depicting iron deficiency, resilience score, and strength and difficulties questionnaire C (SDQ) score depicting EBPs. Methods: A total of 120 adolescents living in Child Care Institutions (CCI) registered under the Juvenile Justice Act (JJ Act) in Chennai, Tamil Nadu, India, will be enrolled in a single-blinded randomized controlled trial. The participants are randomly assigned into intervention (n=60) and control (n=60) groups. The AFIB involves a simultaneous Moringa Amla millet bar (30 g) supplementation (daily) along with life skill training interventions and mindful mandala interventions (weekly).  Results: The primary outcomes are changes in hematological parameters, including hemoglobin (HB), hematocrit (HCT), mean corpuscular volume (MCV), mean corpuscular HB (MCH), mean corpuscular HB concentration (MCHC), and red cell distribution width (RDW); changes in resilience score, measured by Connor Davidson resilience assessment scale (CD-RISC); and strength and problems measured by strength and difficulty questionnaire rated by wardens of the CCIs. The secondary outcomes are changes in anthropometric measures, including height, weight, mid upper arm circumference, and body mass index (BMI). The data will be analyzed using a paired t-test, repeated measures analysis of variance, and descriptive statistics using SPSS software. The significance level will be set at 0.05. Conclusion: The study protocol outlined here sets the foundation for the concept of an adolescent focused intervention bundle and its implications for vulnerable, institutionalised adolescents. The study findings have the potential to significantly influence both clinical practice and future research particularly in developing multifaceted interventions tailored to this population.